CPEB controls the cytoplasmic polyadenylation of cyclin, Cdk2 and c-mos mRNAs and is necessary for oocyte maturation in Xenopus. - Stebbins-Boaz, B (1996)
Cytoplasmic polyadenylation is a key mechanism controlling maternal mRNA translation in early development. In most cases, mRNAs that undergo poly(A) elongation are translationally activated; those that undergo poly(A) shortening are deactivated. Poly(A) elongation is regulated by two cis-acting sequences in the 3'-untranslated region (UTR) of responding mRNAs, the polyadenylation hexanucleotide AAUAAA and the U-rich cytoplasmic polyadenylation element (CPE). Previously, we cloned and characterized the Xenopus oocyte CPE binding protein (CPEB), showing that it was essential for the cytoplasmic polyadenylation of B4 RNA. Here, we show that CPEB also binds the CPEs of G10, c-mos, cdk2, cyclins A1, B1 and B2 mRNAs. We find that CPEB is necessary for polyadenylation of these RNAs in egg extracts, suggesting that this protein is required for polyadenylation of most RNAs during oocyte maturation. Our data demonstrate that the complex timing and extent of polyadenylation are partially controlled by CPEB binding to multiple target sites in the 3' UTRs of responsive mRNAs. Finally, injection of CPEB antibody into oocytes not only inhibits polyadenylation in vivo, but also blocks progesterone-induced maturation. This is due to inhibition of polyadenylation and translation of c-mos mRNA, suggesting that CPEB is critical for early development.